A Guide to Conducting Online Focus Groups via Reddit. (11th May 2021) - Richard, Brendan; Sivo, Stephen A.; Ford, Robert C.; Murphy, Jamie; Boote, David N.; Witta, Eleanor; Orlowski, Marissa
Now more than ever there exists a need to conduct data collection online in a safe environment while ensuring that methodological rigor is not sacrificed. Widely available online platforms allow for text-based focus groups to be conducted quickly, easily, and efficiently, but protocols must be maintained to ensure they do not descend into casual observation of naturally occurring conversations. Various online platform options and their merits are discussed. Reddit is provided as a case study to illustrate the steps through which researchers can conduct an asynchronous online focus group. Key opportunities such as a similar quality of results, a lower cost, easier recruitment, and the ability to accommodate more sensitive topics are discussed, as well as challenges including a stigma against online focus groups, when they are most appropriate, and the potential for deviant behavior.